THE INFLUENCE OF TECHNOLOGY AND SOCIAL MEDIA TO YOUNG INVESTOR INTERESTS TO INVEST WITH INVESTMENT KNOWLEDGE AS A MEDIATING VARIABLE - Dini Prathivi; Antonius Juniarto (FEB Universitas Sam Ratulangi Manado, 2023)
The purpose of this study was to determine how interested young people are in investing by the influence of any knowledge and information they got about the investment itself through the increasing use technology and social media. The study was carried out using quantitative methods as questionnaires distributed to adolescents born in Indonesia between 1996 and 2009. It is hoped that this research will reveal the impact of social media and technology on young investor’s investment interest.